Transforming Culinary MSME Sales through E-Commerce to Strengthen Tourism Villages: A Case Study of Cibeber Village, Purwakarta - Heny Ratnaningtyas; Alda Chairani; Pricilia Johani Sakti; Irfal; Eduard Rudolf Pangkerego (Program Studi Manajemen Divisi Kamar, 2026)
This study aims to analyze the use of e-commerce by culinary MSMEs in Cibeber Village, Purwakarta, to support the development of culinary-based tourism villages. The research focused on identifying barriers, opportunities, and strategic assistance needed to enable MSMEs to transform digitally. The research method used a qualitative approach with a case study design. Data were collected through semi-structured interviews, field observations, and documentation with key informants, culinary MSME owners who had been operating for at least two years. The results showed that most MSMEs still rely on traditional sales through local markets, consignment sales at stalls, and word-of-mouth promotion. Low digital literacy, limited internet infrastructure, and a culture of face-to-face transactions are the main factors inhibiting e-commerce adoption. Nevertheless, MSMEs expressed interest in utilizing the market if training, technical assistance, and better internet access were available. The study's conclusions confirm that digital transformation for culinary MSMEs in Cibeber Village is not merely a necessity but also a strategic opportunity to increase competitiveness and support the village's branding. Research recommendations include implementing ongoing digital literacy training, improving internet infrastructure, providing comprehensive transaction security education, and integrating mentoring based on collaboration among the government, academics, and the private sector